Developing a Research Tool to Measure the Opinion of the University Teachers towards Educational Television Programmes - Jayakumar, R. (American Journal of Education and Learning, 2016)
This research tool focuses on gathering information about the opinion of the university teachers towards educational television programmes. The opinion plays a vital role in effective change in the television during its earliest stage of growth in a given developing country is useful mainly as a means to reach and influence policy makers in urban settings. Television is a powerful media of communication with a tremendous potency to inform, to entertain and to educate. Television can communicate visually through persons, objects, models, pictures, dioramas, diagrams etc. It can communicate aurally through spoken word, music and sound effects. It can also present text, which uses the visual effects, sound effect, It can reproduce the animates and inanimates. It can reproduce rest as well as motion. Television, particularly the digital television can reproduce reality to a large extent. Thus television can produce comprehensive views mixing different stimuli.